Asymmetric syntheses of polyhydroxylated 1-hydroxymethylpyrrolizidines - Brambilla, M (2016)
This thesis is concerned with the development of methodology for the asymmetric syntheses of polyhydroxylated 1-hydroxymethylpyrrolizidines. Chapter 1 introduces the biological activities of pyrrolizidine alkaloids and highlights their importance both in Nature and as therapeutic agents. Selected procedures for the syntheses of these compounds are discussed, with a particular focus on the formation of 1-hydroxymethylpyrrolizidines. Chapter 2 describes studies into the asymmetric syntheses of (–)-isoretronecanol and (–)-trachelantamidine via oxidation of the C=C double bond within two diastereoisomeric 7-aminocyclohept-3-ene-carboxylate substrates via either osmium-mediated dihydroxylation or ammonium-directed epoxidation, followed by oxidative cleavage, N-deprotection and in situ double reductive cyclisation to give the target pyrrolizidine alkaloids. Chapter 3 details the syntheses of three 1-hydroxymethyl-7-hydroxypyrrolizidines via the doubly diastereoselective hydroamination of an enantiopure γ-silyloxy-α,β-unsaturated ester followed by diastereoselective enolate allylation. Oxidative cleavage of the C=C double bonds followed by the application of an N-deprotection and in situ double reductive cyclisation protocol, gave (-)-hastanecine, (-)-turneforcidine and (-)-platynecine. Chapter 4 discusses studies into the aldol reaction of β-amino enolates derived from two differently substituted α,β-unsaturated esters culminating in the asymmetric syntheses of the four 1-hydroxymethyl-2-hydroxypyrrolizidines, (-)-macronecine, (-)-1-epi-macronecine, (-)-petasinecine and (-)-1-epi-petasinecine, and the 1-hydroxymethyl-2,7-dihydroxypyrrolizidine (-)-2-epi-rosmarinecine. Chapter 5 contains full experimental procedures and characterisation data for all compounds synthesised in Chapters 2, 3, and 4.